2019
DOI: 10.1177/0885066619879884
|View full text |Cite
|
Sign up to set email alerts
|

Nonocclusive Mesenteric Ischemia and Interventional Local Vasodilatory Therapy: A Meta-Analysis and Systematic Review of the Literature

Abstract: Background: Intensive care patients with nonocclusive mesenteric ischemia (NOMI) show mortality rates of 70% to 90%. Besides emergency surgery, different interventional local vasodilatory treatment (LVT) attempts have been described. We performed a systematic review and a meta-analysis to evaluate feasibility, efficacy, and tolerability of LVT in patients with life-threatening NOMI. Methods: Searches of PubMed, EMBASE, Web of Science, and Cochrane Library databases were performed until February 2019. Measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…Recently, a systematic review of 12 retrospective studies of interventional local vasodilatory treatment in NOMI reported 40% overall mortality and low treatment-related complication rate of less than 3%. In four comparative studies between patients receiving intra-arterial vasodilator therapy and those who received standard care, the pooled odds of death was significantly lower for those receiving the experimental therapy ( 20 ). Another interesting experimental treatment that may be worth studying further is the administration of prostaglandin or iloprost intravenously to improve the hepato-splanchnic blood flow and oxygen intake in NOMI ( 21 , 22 ).…”
Section: Nomimentioning
confidence: 99%
“…Recently, a systematic review of 12 retrospective studies of interventional local vasodilatory treatment in NOMI reported 40% overall mortality and low treatment-related complication rate of less than 3%. In four comparative studies between patients receiving intra-arterial vasodilator therapy and those who received standard care, the pooled odds of death was significantly lower for those receiving the experimental therapy ( 20 ). Another interesting experimental treatment that may be worth studying further is the administration of prostaglandin or iloprost intravenously to improve the hepato-splanchnic blood flow and oxygen intake in NOMI ( 21 , 22 ).…”
Section: Nomimentioning
confidence: 99%
“…Papaverine and prostaglandin E1 are the most commonly used agents, but their availability is limited. 14) Winzer et al reported that local intra-arterial infusion of papaverine in patients with NOMI significantly increased survival in comparison with conservative treatment. However, this study also reported that high lactate levels, low pH and high base excess, and high demand for catecholamines were associated with poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality associated with NOMI remains unchanged exceedingly high up to above 90% (3,4). NOMI accounts for up to 15% of acute mesenteric ischemia cases (5) and is characterized by functional vasoconstriction of the superior mesenteric artery (SMA) and its smaller branches in the absence of an intraluminal obstruction (2,4,5). Spasm of these mesenteric vessels leads to signi cantly reduced perfusion of the intestine and consequently, mesenteric ischemia, which may result in transmural necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…This process triggers a secondary systemic in ammatory response that may result in remote organ failure (7). NOMI occurs typically in the context of shock, especially following cardiac surgery (1)(2)(3)(4), in low output heart failure (1,2,4), and a variety of heterogeneous acute critical illnesses all requiring high dose vasopressor therapy such as septic shock (2)(3)(4)8). Various preexisting comorbidities, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation